A cryptic palm-pitviper species (Squamata: Viperidae: Bothriechis) from the Costa Rican highlands, with notes on the variation within B. nigroviridis - Doan, Tiffany M.; Mason, Andrew J.; Castoe, Todd A.; Sasa, Mahmood; Parkinson, Christopher L. (Zootaxa, 2016)
Middle America is one of the most biodiverse regions in the world, harboring an exceptional number of rare and endemic species. This is especially true of Middle American cloud forests, where montane specialists occupy restricted, high-elevation ranges making them attractive candidates for investigating historical biogeography and speciation. One such highland-restricted species, the black speckled palm-pitviper (Bothriechis nigroviridis), occupies the Central, Tilarán, and Talamanca Cordilleras in Costa Rica and Panama. In this study, we investigate the genetic and morphological variation among populations of B. nigroviridis by inferring a multilocus phylogeny (21 individuals) and analyzing meristic scale characters with a principal component analysis (64 individuals). We find B. nigroviridis sensu stricto to be composed of two deeply divergent lineages, one with a restricted range in the northern and central Cordillera Talamanca and the other ranging throughout the Central, Tilarán, and Talamanca Cordilleras. Furthermore, these two lineages are morphologically distinct, with previously unrecognized differences in several characters allowing us to name and diagnose a new species B. nubestris sp. nov. We also examine the genetic and morphological variation within B. nigroviridis and discuss biogeographic hypotheses that may have led to the diversification of Bothriechis lineages.